+0  
 
0
451
2
avatar

∆U=2*I*L/Y*A nach A umstellen

 30.03.2017
 #1
avatar+8459 
+1

∆U=2*I*L/Y*A nach A umstellen

 

 

\(Deutung A:\)

 

\(\Delta U=2*I*\frac{L}{Y}*A\)      [beidseitig \(\times \frac{Y}{2\times I\times L}\)

 

\(A=\frac{\Delta U*Y}{2*I*L}\)

 

\(Deutung B:\)

 

\(\Delta U=2*I*\frac{L}{Y*A}\)        [beidseitig \(\times\frac{A}{\Delta U}\)

 

\(A=\frac{2*I*L}{\Delta U*Y}\)  

 

laugh  !

 30.03.2017
 #2
avatar
0

A=2*I*L/U*Y

Freundliche Grüsse :)

 31.03.2017

17 Benutzer online